2019
DOI: 10.1111/pala.12433
|View full text |Cite
|
Sign up to set email alerts
|

The giants of the phylum Brachiopoda: a matter of diet?

Abstract: The species of the brachiopod Gigantoproductus are giants within the Palaeozoic sedentary benthos. This presents a dilemma as living brachiopods have low‐energy lifestyles. Although brachiopod metabolic rates were probably higher during the Palaeozoic than today, the massive size reached by species of Gigantoproductus is nevertheless unusual. By examining the diet of Gigantoproductus species from the Visean (Mississippian, Carboniferous) of Derbyshire (UK), we seek to understand the mechanisms that enabled tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 113 publications
(190 reference statements)
5
16
0
1
Order By: Relevance
“…In the shallow‐water populations, some of the very large specimens in this study are the largest reported for the species. Similar gigantism of brachiopods has been reported (see Rong et al for a brief review), such as Gigantoproductus from the Carboniferous (Qiao & Shen ; Angiolini et al ), suggesting that only the most suitable environments for these populations can promote the largest body size.…”
Section: Discussionsupporting
confidence: 64%
“…In the shallow‐water populations, some of the very large specimens in this study are the largest reported for the species. Similar gigantism of brachiopods has been reported (see Rong et al for a brief review), such as Gigantoproductus from the Carboniferous (Qiao & Shen ; Angiolini et al ), suggesting that only the most suitable environments for these populations can promote the largest body size.…”
Section: Discussionsupporting
confidence: 64%
“…S7C); parallel growth lines were also found in cross‐section, which are comparable with previous observations (Angiolini et al . 2012, 2019; Garbelli 2017). An alternation of secondary and tertiary layer was observed only in Uchtospirifer aff.…”
Section: Discussionmentioning
confidence: 99%
“…2008), instead, productids show taxa with shell thickened by thin laminae with a sub‐micrometric thickness, as well as producing thick prismatic layers (Angiolini et al . 2012, 2019; Garbelli 2017). In any case, there is never a simple solution such as obtaining a thicker shell by increasing the size of its structural units, as in our data set there is no correlation between shell thickness and fibre/laminae thickness at specific level, nor in most of the orders (Table 5), except for the Orthida which shows a negative correlation at the limit of significance ( p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Gigantoproductids (tribe Gigantoproductini [30]) are key due to its great potential for paleoclimatological studies because: i) frequent during Carboniferous [28,31,32]; ii) global distribution [30]; iii) large shell thickness and size [33], which allow the extraction of material for geochemical analyses easier than other fossil brachiopods [28,34,35]. Large shell size has been attributed to a possible a chemosymbiotic lifestyle [35]. In spite of these advantages, few studies have been focused on this fossil group for paleoclimatological purposes [9,17,22,28,34].…”
Section: Introductionmentioning
confidence: 99%
“…Growth rate and stable isotopic fractionation covariation have been identified in δ 18 O and δ 13 C in extant and fossil brachiopods [24,35,40,[49][50][51][52]. δ 18 O and δ 13 C variations between shell layers have been documented in extant and fossil brachiopods, which were considered as kinetic effects of the shell growth [24,43,[49][50][51].…”
Section: Introductionmentioning
confidence: 99%